The Impact of Participation in Research About Abuse and Intimate Partner Violence: An Investigation of Harms, Benefits, and Regrets in Young Adolescents in the Western Cape of South Africa. Issue 3 (February 2020) - McClinton Appollis, Tracy; Eggers, Sander Matthijs; de Vries, Petrus J.; de Vries, Hein; Lund, Crick; Mathews, Cathy
There is very little evidence whether recalling and answering questions about abuse or interpersonal violence has a positive or negative impact on participants of such research. This is an important ethical dilemma to ensure an appropriate risk-benefit ratio in research with young people is maintained. We assessed reported harms, benefits, and regrets of young adolescents who participated in a sensitive research project, and compared the harms and benefits in those who had and had not been victims and/or perpetrators of abuse or intimate partner violence. Participants were 3, 264 adolescents aged 12 to 15 years in 41 public schools in the Western Cape, South Africa, who completed a survey about intimate partner violence, verbal, physical, and sexual abuse, as part of an HIV prevention cluster randomized controlled trial. The majority of participants reported research participation as beneficial (70.3%), while 27.7% reported harms and 14% regrets. Victims of abuse were more likely than non-victims to report benefits (71.9% vs. 67.1%; p = .02) and harms (31% vs. 20.9%; p < .01) and were less likely to report regret (13.1% vs. 16.7%; p = .02). Perpetrators of abuse were less likely than non-perpetrators to report benefits (67.4% vs. 72.8%; p = .01) and more likely to report harms (36.4% vs. 26.1%; p < .01) and regrets (17.4% vs. 13.3%; p = .01). Our findings suggested that research participation was more likely to have a positive rather than a negative emotional impact on young adolescents and that relatively few regretted participating. Victims and perpetrators of abuse were more likely to report benefits than harms, supporting the ethical appropriateness of ongoing research on abuse and violence. We recommend that further research is required to clarify and standardize terminology and instruments to quantify these kinds of evaluations, including measurement of the severity and intensity of reported benefits, harms and regrets, and the longer term impact of participation in sensitive research.